1981
DOI: 10.2134/jeq1981.00472425001000030001x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Transport of Microbial Pathogens and Indicator Organisms in Soils Treated with Organic Wastes

Abstract: In a critical review of pathogen and indicator-organism transformations and transport from land areas receiving organic wastes, microbial die-off was described assuming first-order kinetics. First-order die-off rate constants (k) were calculated from the literature data for various pathogens and indicator organisms. For indicator organisms average die-off.rates were 1.14 day-' (0.08-9.1) for fecal coliforms, and 0.41 day-' (0.05-3.87 day-') for fecal streptococci. For pathogens, the average die-off rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(150 citation statements)
references
References 0 publications
8
139
1
2
Order By: Relevance
“…We found that decreasing soil moisture with increasing soil temperature substantially decreased survival of total and fecal coliform bacteria in all three soil depths examined. Reddy et al (1981) found that fecal coliform bacteria dieoff follow first order kinetics and that the two most important factors influencing survival were moisture a8d temperature. Soil moisture seems to be the most important of these factors (Sjogren, 1994;Crane and Moore, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that decreasing soil moisture with increasing soil temperature substantially decreased survival of total and fecal coliform bacteria in all three soil depths examined. Reddy et al (1981) found that fecal coliform bacteria dieoff follow first order kinetics and that the two most important factors influencing survival were moisture a8d temperature. Soil moisture seems to be the most important of these factors (Sjogren, 1994;Crane and Moore, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Soil temperature also exerts a major influence on the survival of pathogenic bacteria. Extremely hot (>28°C) soil temperatures combined with drying will effectively decrease survival rates (Sjogren, 1994;Reddy et al, 1981). The objective of this study was to determine the survival of total and fecal coliform bacteria in soil growing three different types of riparian vegetation in different climatic conditions.…”
mentioning
confidence: 99%
“…), hydrodynamic profile (oxygen concentration, residence time in filter) and microbial niche control the fate of microbes when applied on to the soil (Reddy et al, 1981;Crane and Moore, 1984). Pathogen removal in CSF system is due to (i) property of media to retain pathogens in first phase of filtration, i.e.…”
Section: Pathogen Removalmentioning
confidence: 99%
“…We assume that the function R(r) can be estimated from literature data on the probability distribution of E. coli O157 in fresh cattle faeces, combined with a deterministic estimate of total E. coli content of cattle faeces (we used the log value per gram faeces of 5.36 (Reddy et al, 1981)), and the value of R(r) is assumed to have an upper bound of 1. The E. coli O157 content of cattle faecal pats on 88 E. coli O157-positive Scottish farms (18% of farms sampled) has been quantified by Halliday et al (2006).…”
Section: Risk Of Infectionmentioning
confidence: 99%